Challenges Facing Effective Implementation of Free Primary Education in Public Primary Schools: A Case Study of Githunguri District Kiambu County - Kinyanjui, Monica; Ishmail, Mwasa; Mbutu, Phyllis (My University, 2014)
The purpose of the study was to determine the challenges facing implementation of free primary education in Kenya today using Githunguri district in Kiambu County as a case study. The study sought to identify the factors that have lead to poor implementation of the free primary education. The target population is the 30 public primary schools in the district. A census method of data collection was used. The study revealed that public primary schools in Githunguri district are facing numerous challenges in terms of performance, administrative, and financial. This have in turn impacted negatively on the smooth implantation of the program.
Keywords: Free primary education; public primary school